Surgical management of staple line leak after laparoscopic sleeve gastrectomy - Mukhtar, Ramiz S.; AbdulJabbar, Mohammed Q. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Laparoscopic sleeve gastrectomy (LSG)is derived from the biliopancreatic diversion with duodenal switch operation(BPD-DS). Specific and potentially severe complications of LSG are bleeding from the staple line and staple line leakage (SLL). A staple line leak may result in severe morbidity with potential sepsis and multi- organ failure. Objectives: To review our experience with the definitive surgical management of staple line leak Post sleeve gastrectomy and its outcomes. Patients and methods: retrospective review of patients who underwent definitive surgical treatment of staple line leak post sleeve gastrectomy from May 2014 till June 2016 at Saint Raphael center of morbid obesity, Primary surgery was laparoscopic sleeve gastrectomy in all patients. Staple line leak was diagnosed at the gastroesophageal junction in all patients. Results: Six female patients were treated with definitive surgical management, mean body mass index was 42.7±4.0(range from 35.3-51.2 kg/m2 ), all patient had no associated co-morbidities related to obesity, the mean age of the patients was 36(range from 29-43 years), The leak was at the Gastroesophageal junction in all patients.All patients were fully recovered after definitive surgical treatment of leak, no signs of persist leak during the follow up period, with no mortality Conclusions: Definitive surgical repair with conversion to Roux-en-Y gastric bypass, is safe and very effective and should be done when the general condition of the patient is optimized whenever possible.